Changes in Women’s Political Participation in the 2024 General Election in Malang City - Siti Kholifah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Women's participation in politics remains a significant issue, despite the emphasis on gender equality in political party administration since 2002 and the encouragement of a 30% legislative quota for women in 2003. Women continue to encounter substantial challenges when entering the political sphere. Data from the Indonesia Statistics of Malang City indicate that the percentage of women in the legislature remains below 30%. In the 2019 Election, political participation among Malang's citizens reached 77.5%. This research investigates whether there are differences in women's political participation in Malang City between the 2019 and 2024 elections and explores the changes in the 2024 Election. Employing the participation concept used by the General Election Supervisory Agency to measure the Election Vulnerability Index, this study adopts an explanative qualitative approach with the women of Malang City as the research population. Data collection was conducted through interviews, documentation, and observation. The data were analyzed using the Wilcoxon statistical test. The research results indicate significant differences in the levels of women's political participation between the 2019 and 2024 Elections, with a significance level of 0.05. Although the political participation of women in these elections is still categorized as low, this is attributed to women's apathy towards political conditions and the perception of politics as a male domain, as well as the complex monitoring report mechanisms. Women perceive the political sphere as harsh and unsuitable, further influenced by stereotypes that emphasize femininity and domestic roles, which encourage passive behavior in political arenas.